Big schools of small fish in a big pond – the influence of small-island developing states in the BBNJ process - Kahlil Hassanali; Nellie Catzim; Ríán Derrig; Harriet Harden-Davies; Vui Gemma Nelson; Angelique Pouponneau (Frontiers in Marine Science, 2026)
Small Island Developing States (SIDS) are champions on the global stage of sustainable and equitable ocean management. This paper addresses the contributions of SIDS to the negotiation and development of the legally binding agreement under the United Nations Convention on the Law of the Sea (UNCLOS) on the Conservation and Sustainable Use of Marine Biological Diversity of Areas beyond National Jurisdiction (BBNJ Agreement). Firstly, we reflect on how SIDS claimed space and asserted voice during the negotiation process. We illustrate SIDS’ emergence as active, effective and influential participants in the BBNJ negotiation process, highlighting issues key for SIDS such as special circumstances of SIDS as a principle, special considerations relating elements of the Agreement’s package, and representation on key institutional structures. Secondly, we analyse how and why SIDS created space and gave voice to important topics for equity in the agreement - such as transparency, participation, traditional knowledge, gender, and effective capacity building and technology transfer. We argue that these contributions by SIDS stand to benefit the implementation of the agreement as a whole. Thirdly, we look ahead to consider how SIDS might cement space and maintain voice, including in relation to promoting SIDS expertise in implementation, enabling knowledge exchange between SIDS negotiators, and filling capacity and financing shortfalls in SIDS. Our analysis illustrates a strategic approach of internal coordination geared towards targeted external influence that served SIDS well during the negotiations and stands to benefit SIDS and the ocean overall in future.